Circulating in the blood desquamated endotheliocytes at the cardiovascular diseases. Preliminary communication - Anatoliy Gozhenko; Hanna Pavlega; Nataliia Badiuk; Walery Zukow (Nicolaus Copernicus University in Toruń, 2024)
Introduction and aim. We previously found that diabetic angiopathy is accompanied by an increase in the level of desquamated endothelial cells (CECs) circulating in the blood, commensurate with its severity. In this study, we set ourselves the aim of analyzing the level of CECs in patients with cardiovascular pathology and their relationship with the level of blood pressure and routine clinical indicators. Material and methods. The object of clinical observation were patients with stage II hypertension, who were receiving outpatient treatment. Among them, 23 men (62.3±13.2 ys) and 39 women (65.1±10.6 ys). Concomitant ischemic heart disease was diagnosed in 16 men (70±10%) and 28 women (72±7%). The main subject of the study was blood pressure and the level of CECs. In addition, routine general blood analysis and determined metabolic parameters were performed. Results. Using the method of cluster analysis, the sample was divided into 4 homogeneous groups, different from each other. It was found that in 18 patients of the first cluster, the youngest in the sample, the minimum level of hypertension for the sample occurs against the background of unchanged CECs levels and other registered parameters, instead, it is accompanied by moderate increased creatininemia and a significantly increased rate of erythrocyte sedimentation and a reduced level of hemoglobin and color index. In 18 patients of the second cluster, moderately elevated levels of terminally and markedly changed CECs were found in combination with minimally expressed signs of hyperchromic anemia. In the third cluster (n=16), the levels of terminally and markedly changed CECs are significantly increased in combination with a reduced level of urea and LP index against the background of moderate hyperchromic anemia. Finally, in 10 patients of the fourth cluster, the oldest in the sample, with maximally expressed hypertension, it is accompanied by maximally elevated levels of all three types of СEСs against the background of moderate hyperchromic anemia. Conclusion. Desquamated plasma endothelial cells can be one of the criteria for the severity of hypertonic disease.